HUBUNGAN PATRON KLIEN DALAM KOMUNITAS NELAYAN (Studi Kasus di Pelabuhan Perikanan Pantai Sadeng Kabupaten Gunung Kidul) - Raya Surya Samudera; Rahesli Humsona (Journal of Development and Social Change, 2018)
Abstract : The research about the relationship between client patron employer boat owners as patron and fishermen as a client. The purpose of this study is to describe the relationship between the client employer patron boat owners with the fishermen, starting from recruitment process work and contract work of fishermen, the system of wages, health coverage, and hours of work that applies in his work . This study uses social exchange theory of g. Homans and patron client theory of James Scott. The methods used in this research is qualitative method with approach case studies. Informants in this study consists of employer's boat owners, fishermen, and the head of the harbour fishing port Sadeng beach. For sampling using a purposive sampling technique. The location of this research is the fishing port Sadeng Beach Regency of Gunung Kidul. Engineering data collection done way interview, observation, and study the documentation. Data analaisis techniques used are interactive models, Miles and Huberman that started from the collection of data, data presentation, data reduction and withdrawal of the conclusion. For the validity of data using triangulation of sources. The results showed that the social exchange that took place between the employer ship owners who have capital, capture tool, and the ship, with fishermen who had the ability to catch fish is mutually satisfy the needs of both parties. This relationship is elementary, where economic transactions in this working relationship going on exchanges between the capital services. The employer gives ship owners the assurance of basic subtensi in the form of employment, the guarantee of economic crisis in the form of a loan of money, health coverage by taking all treatment of fishermen, ship care protection with the routine, and Realtor and influence in the document management of the ship. While the fishermen provided services basic job as a fisherman, and became a member of loyal patrons.Keywords : Patrons, clients, fishermanAbstrak: Penelitian tentang hubungan antara pemilik patron pemilik kapal patron klien sebagai patron dan nelayan sebagai klien. Tujuan dari penelitian ini adalah untuk mendeskripsikan hubungan antara pemilik kapal patron klien majikan dengan nelayan, mulai dari proses rekrutmen kerja dan kontrak kerja nelayan, sistem upah, cakupan kesehatan, dan jam kerja yang berlaku dalam pekerjaannya. Penelitian ini menggunakan teori pertukaran sosial g. Homans dan teori klien pelindung James Scott. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Informan dalam penelitian ini terdiri dari pemilik kapal pengusaha, nelayan, dan kepala pelabuhan nelayan pelabuhan pantai Sadeng. Untuk pengambilan sampel menggunakan teknik purposive sampling. Lokasi penelitian ini adalah pelabuhan perikanan Pantai Sadeng Kabupaten Gunung Kidul. Teknik pengumpulan data dilakukan dengan cara wawancara, observasi, dan studi dokumentasi. Teknik analaisis data yang digunakan adalah model interaktif, Miles dan Huberman yang dimulai dari pengumpulan data, penyajian data, reduksi data dan penarikan kesimpulan. Untuk keabsahan data menggunakan triangulasi sumber. Hasil penelitian menunjukkan bahwa pertukaran sosial yang terjadi antara pemilik kapal majikan yang memiliki modal, alat tangkap, dan kapal, dengan nelayan yang memiliki kemampuan menangkap ikan saling memenuhi kebutuhan kedua belah pihak. Hubungan ini adalah dasar, di mana transaksi ekonomi dalam hubungan kerja ini terjadi pada pertukaran antara layanan modal. Pemberi kerja memberi pemilik kapal jaminan substitusi dasar dalam bentuk pekerjaan, jaminan krisis ekonomi dalam bentuk pinjaman uang, jaminan kesehatan dengan mengambil semua perawatan nelayan, perlindungan perawatan kapal dengan rutin, dan Realtor dan pengaruh dalam manajemen dokumen kapal. Sedangkan nelayan menyediakan jasa pekerjaan dasar sebagai nelayan, dan menjadi anggota patron yang loyal.Kata kunci: Pembina, klien, nelayan